1994
DOI: 10.1161/01.res.74.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemia and reperfusion on cardiac ryanodine receptors--sarcoplasmic reticulum Ca2+ channels.

Abstract: We investigated the effect of ischemia and reperfusion on the cardiac ryanodine receptor, which corresponds to the sarcoplasmic reticulum Ca2+ channel. Isolated working rat hearts were subjected to 10 to 30 minutes of global ischemia, followed or not by reperfusion. Ischemia produced significant reduction in the density of high-affinity 3H-ryanodine binding sites, determined either in whole-heart homogenate (Bmax, 220 +/- 22, 203 +/- 12, and 228 +/- 14 fmol/mg protein after 10, 20, and 30 minutes of ischemia v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…This finding is in agreement with previous studies. [6][7][8]10 Daring et al observed a reduction in the Bmax for ryanodine after 60 min of ischemia, but could not conclude that the density of SR channels was affected by ischemia because of contamination by myofibrillar protein. 6 However, Zucchi et al reported that myofibrillar contamination, as estimated by K-ATPase activity, was not different in SR preparations obtained from controls or after 20 min of ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is in agreement with previous studies. [6][7][8]10 Daring et al observed a reduction in the Bmax for ryanodine after 60 min of ischemia, but could not conclude that the density of SR channels was affected by ischemia because of contamination by myofibrillar protein. 6 However, Zucchi et al reported that myofibrillar contamination, as estimated by K-ATPase activity, was not different in SR preparations obtained from controls or after 20 min of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, Zucchi et al reported that myofibrillar contamination, as estimated by K-ATPase activity, was not different in SR preparations obtained from controls or after 20 min of ischemia. 7 In the present study, we purified the enriched fraction of the SR vesicles for the binding assay because a previous study showed that this successfully avoided contamination by myofibrillar proteins. The smaller reduction in ryanodine binding seen in the CA group indicated that the number of receptors in the functional state was much better preserved during cardioplegic arrest and reperfusion than during global ischemia -reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After injection of 1000 U sodium heparin in the femoral vein, the heart was quickly excised and perfused according to the working heart technique, as described previously. 43 The height of the atrial and aortic cannulae was set at 20 and 100 cm, respectively. Unless otherwise specified, the perfusion buffer included (mM): 118 NaCl, 25 NaHCO 3 , 4.5 KCl, 1.2 KH 2 PO 4 , 1.2 MgSO 4 , 1.5 CaCl 2 , and 11 glucose.…”
Section: 51 (N)mentioning
confidence: 99%